Proyecto de Inversión y su Incidencia en la rentabilidad para la creación de una envasadora y distribuidora de agua, Cantón Buena Fe, año 2014 - Aragundi Lirio, Cristina Jacqueline (2015)
This work is a "INVESTMENT PROJECT AND ITS IMPACT ON PROFIT FOR THE CREATION OF A PACKAGING AND DISTRIBUTION OF WATER, CANTON GOODWILL, 2014." The development seeks to meet current demand due to the absence of a water purification . The market survey showed that there is an unmet demand with the product they are receiving in Canton Good Faith, for this reason the results of the research have a favorable acceptance for project implementation. The technical study carried out for the project, announced the investment necessary for its development, with an investment of $ 131.635.00 it includes fixed assets, production costs, etc. A financial study was applied to the investment project to meet its profitability NPV positive results it shows an amount of $ 56.375.71, followed by an Internal Rate of Return (IRR) of 57% which is the average of expected future returns by that investment, in the same way the Benefit Cost (B / C) with a value of $ 1.78 means that for every dollar invested will receive $ 0.78 cents resulting in a Net Income of $ 12.840.86 for the first year showing that the investment project to be implemented has excellent profitability.